Pedestrian disconnect across downtown highways - May, Douglas (Kansas State University, 2016)
This study seeks to investigate the impact of inner-city highways on walkability in urban downtowns in the United States, using Greater Downtown Kansas City as a case study. This study used the web-based online survey method to assess if inner-city highways impede the flow of pedestrians among residents and visitor of the Greater Downtown Kansas City, Missouri. The results showed that there were differences in the perception of the pedestrian environment between residents and visitors of the downtown area. Downtown residents generally had a more favorable view of the pedestrian environment than visitors of Greater Downtown. Additionally, the inner-city highways did not appear to be barriers to pedestrian mobility, which differs from the hypothesis of this study. However, although the pedestrian overpasses over the highways did have an impact on pedestrians’ perceptions and walking behaviors, newer overpasses with wider sidewalks mitigated barrier effects of highways more than older overpasses with narrow sidewalks. The study also found that walking was the most common travel mode for all trips in Greater Downtown Kansas City, despite potential barriers.
Keywords: Pedestrian; Kansas City; Downtown; Mobility; Highway; Walkability